Comparative assessment of polyphenol stability, bioactivity, and digestive availability in purified compounds and fruit extracts from four black chokeberry cultivars - Sabina Lachowicz-Wiśniewska; Michał Świeca; Ireneusz Kapusta; Anna Sip; Ireneusz Ochmian (Scientific Reports)
Abstract This study evaluated the stability and biological activity of polyphenols in purified polyphenolic extract (IPE) and fruit matrix extract (FME) from four black chokeberry cultivars during in vitro digestion. Fifteen polyphenolic compounds were identified in both extracts by UPLC-PDA-MS/MS, with similar qualitative profiles but quantitative differences. This is the first comparative analysis of IPE and FME from four cultivars—Nero, Viking, and the newly characterized Aron and Hugin. The aim was to assess their antioxidant, anti-inflammatory, antimicrobial, and prebiotic properties across the gastric, intestinal, and absorptive phases. Multivariate statistical analysis (PCA/HCA) was used to evaluate digestion- and cultivar-specific patterns. Anthocyanins dominated the polyphenol profile (79%), while flavonols represented 6%. The highest total polyphenol content was found in the FME of cv. Nero (38.9 mg/g dry matter (d.m.)). Despite containing 2.3 times fewer polyphenols, IPE showed superior bioactivity, including 1.4–3.2 times higher antioxidant potential (FRAP, OH·), up to 6.7-fold stronger inhibition of LOX, and 3–11 times higher bioaccessibility and bioavailability indices across polyphenol classes. These enhancements were likely due to enrichment in more stable phenolic acids and flavonols and the removal of interfering matrix components. Simulated digestion resulted in a 20–126% increase in polyphenol content during the gastric and intestinal stages in IPE, followed by ~ 60% degradation post-absorption, whereas FME showed a 49–98% loss throughout digestion. IPE also exhibited higher bioavailability indices for antioxidant and anti-inflammatory activities. Moreover, the Viking cultivar demonstrated antimicrobial activity against Candida albicans, Escherichia coli, Listeria monocytogenes, and Yersinia enterocolitica. These findings highlight the functional potential of purified polyphenol extracts from black chokeberry and their relevance for the development of stable and bioavailable nutraceutical ingredients.